n Kritiese evaluering van die opleiding van die Ned. Geref. predikant - Knobel, Robert Frank,1962- (Stellenbosch : Stellenbosch University, 2012)
Verhandeling (B. Th.) -- Universiteit van Stellenbosch, 1988.